151k views
0 votes
Helppppppppppp meeeee​

Helppppppppppp meeeee​-example-1

1 Answer

3 votes

Answer:

y = -2x + 3

Explanation:

Let's just put the three points together.

(-1, 5) (-4, 11) (-7, 17)

First, let's find the slope with y2 - y1/x2 - x1

Plug in using (-1, 5) and (-4, 11)

11 - 5/-4 + 1 = 6/-3 (simplify)

-2 is the slope

Now plug in (-7, 17) in the equation to get b or the y-intercept)

y = mx + b

17 = -2(-7) + b

17 = 14 + b (subtract 14 on both sides)

3 = b

y = -2x + 3

User Dimbslmh
by
5.2k points